Basura : Cultures of Waste in Contemporary Spain - Amago, Samuel, 1974- (Book collections on Project MUSE., 2021)
"An exploration of how Spanish culture has engaged with the debris it has created and cast aside, this book reveals the problematic, ever evolving process of discarding and, inevitably, of recovering meaning and value in contemporary Spain"--